Evaluating the qualitative characteristics and heavy elements of hospital water and their relationship with bioresistance in P. aeruginosa - Al-Hashimi, Omar; Saeed, Ibrahim Omar; Lateef Al Meani, Safaa Abed (Technium BioChemMed, 2024)
ABSTRACT: Bacteria use the elements present in the environment to develop their vital defenses, trying to acquire genes from other strains or absorb heavy metals in order to adapt to them and increase their tolerance against high concentrations of heavy elements. Pseudomonas aeruginosa is an opportunistic bacterial pathogen that causes infections in hospitals and communities, including in humans and animals. P. aeruginosa's adaptability and endurance in therapeutic settings are cause for concern. Emerging pathogenic strains pose a global threat and cause significant concern. Biocides are commonly used to control the spread of resistant strains of P. aeruginosa. However, tolerance to these biocides has been reported, which hinders their effectiveness in clinical settings. This study focused on the factors contributing to the persistence of hospital-acquired P. aeruginosa, including its resistance to antibiotics and biocides and the role of heavy metals in the development of increased bacterial resistance to antimicrobials.